A Cost‐Effective Approach to Fabricate Superhydrophobic Coatings Using Hydrophilic Materials1 . Issue 4 (9th September 2015) - Gong, Xiao; Bartlett, Austin; Kozbial, Andrew; Li, Lei
Abstract : Superhydrophobic coatings have many important applications and previous studies have shown that both hydrophobic material and certain surface topographical features are required to achieve the desired superhydrophobicity. Here, we report a simple and cost‐effective approach to fabricate superhydrophobic coatings using alumina powders, which are intrinsically hydrophilic. The water contact angle (WCA) of the coating is close to 150° and the observed superhydrophobicity has been attributed to both the powder‐induced surface topographical features and the airborne hydrocarbon contamination. This work provides a facile yet robust approach to fabricate superhydrophobic coatings, which is potentially applicable for many other hydrophilic materials. Abstract : Here the authors report a simple and cost‐effective approach to fabricate superhydrophobic coatings using alumina powders, which are intrinsically hydrophilic. This work provides a facile yet robust approach to fabricate superhydrophobic coatings, which is potentially applicable for many other hydrophilic materials.